Transcriptome Analysis Reveals the Flexibility of Cordycepin Network in Cordyceps militaris Activated by L-Alanine Addition - Chen, Bai-Xiong; Wei, Tao; Xue, Ling-Na; Zheng, Qian-Wang; Ye, Zhi-Wei; Zou, Yuan; Yang, Yi; Yun, Fan; Guo, Li-Qiong; Lin, Jun-Fang (Frontiers in Microbiology, 2020)
Cordycepin, isolated from the traditional medicinal fungus Cordyceps militaris, has gained much attention due to its various clinical functions. Previous reports of L-alanine addition could significantly improve cordycepin production, but the molecular mechanism remains unknown. In this study, transcriptome analysis of C. militaris with doubled cordycepin production induced by L-alanine addition provides an insight into the flexibility of the cordycepin network. The biopathways of energy generation and amino acid conversion were activated so that cordycepin substrate generation was consequently improved. Specific genes of rate-limiting enzymes in these pathways, as well as related transcription factors, were figured out. Two key Zn2Cys6-type transcription factors CmTf1 and CmTf2 were verified to be the roles of doubling the cordycepin production by over-expression of their coding genes in C. militaris wild type. These results provide a complete map of the cordycepin network in C. militaris with a distinct understanding of the flexibility of joints, giving a better foundation for increasing cordycepin yield and strain breeding in the future.